THE ROLE OF CRITICAL THINKING DURING FORMATION OF A NEW CULTURAL NARRATIVE - Austruma, Spodra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
During recent years in Latvian society the activities, communication and interaction of different society groups and non-governmental organizations have been increasing at a very high level. The reason for this lies in powerful migration processes in Europe, refugee crisis, political-economical fluctuations in the world, Brexit*, and many other events. Non-formal communication practice has also activated in the space of mass media among different communities, school environment and society as a whole. As a reaction to cultural-political events, utilitarian arguments have gained popularity, where their motives of further delivery are based on stereotypical, easily perceivable opinion that is popular in society, on expressions of utilitarian argumentation, dominating childish simplicity, which directly starts to touch all cultural systems, including education, thus creating new cultural narrative. Emotions are often replacing rational analysis of education and culture - consequently reducing the ability to evaluate through arguments the importance of processes in particular cultural space. Also coordination and change of value priorities of different generations are connecting with the change of cultural and human existence necessity - by changing feelings towards specific values, a group of values from other cultures is growing, where people are required to change their overall thinking (Inglhert,R.Pippa,N.2009,227). Both theoretical and empirical instruments are used in the paper. In order to form theoretical understanding of the problem, normative acts and literature were analysed, strategies of acquisition of information by individual and society were reviewed, individual's desire and ability to use critical thinking were analyzed, which through the search of balance between the truth and stereotypes is creating a new cultural message.